Challenging the Public Service Remit: A Cross-National Comparison of Guidelines for PSM Multiplatform Journalism - Rothberg, Danilo [UNESP]; Seridorio, Daniele Ferreira [UNESP]; Da Silva, Sivaldo Pereira; Speck, Dominik (Usc Annenberg Press, 2024)
Public Service Media (PSM) organizations have been adapting to the introduction of digital technology and multiplatform opportunities over the past 2 decades. This process, conceptualized as a shift from Public Service Broadcasting to PSM, is intended to revitalize the public service mission. Although this movement has been well documented, we noted a lack of studies on how public broadcasters had to develop editorial guidelines to implement strategies effectively and establish leadership in a competitive media landscape. We sought to fill this research gap by applying a comparative, qualitative document analysis to assess how 11 PSM organizations from 10 countries articulated these strategies in editorial guidelines and related documents. The results indicated that all 11 broadcasters fulfilled at least one criterion for assessing multiplatform journalism documentation. However, the degree of centrality varied considerably. Our data suggest that a solid track record of investment and a central position in the national media landscape may drive PSM providers to perform better in terms of the transparency and comprehensiveness of multiplatform journalism policies.
Keywords: public service media; transparency; editorial guidelines; multiplatform journalism